Pregnancy and Labour After Transplantation of Frozen-Thawed Human Embryos - Grischenko, V. I.; Petrushko, M. P.; Gerodes, A. G.; Terpyachaya, I. V.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2003)
There was described the case of pregnancy and labour onset after transferring the frozen-thawed human embryos, frozen by slow program with 1,2- propanediol and sucrose.